2011
DOI: 10.1377/hlthaff.2010.1277
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Pay-For-Performance In Hospitals: Lessons For Quality Improvement

Abstract: The payment approach known as "pay-for-performance" has been widely adopted with the aim of improving the quality of health care. Nonetheless, little is known about how to use the approach most effectively to improve care. We examined the effects in 260 hospitals of a pay-for-performance demonstration project carried out by the Centers for Medicare and Medicaid Services in partnership with Premier Inc., a nationwide hospital system. We compared these results to those of a control group of 780 hospitals not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
174
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(185 citation statements)
references
References 31 publications
5
174
1
3
Order By: Relevance
“…size of incentive, rules linking performance scores to performance payments) [217][218]. It would be necessary to evaluate its effectiveness for improvement purposes in the future.…”
Section: Implications For Policymentioning
confidence: 99%
“…size of incentive, rules linking performance scores to performance payments) [217][218]. It would be necessary to evaluate its effectiveness for improvement purposes in the future.…”
Section: Implications For Policymentioning
confidence: 99%
“…Interest in the use of increasingly sophisticated technology for monitoring MA is not limited to clinical trials. In health care clinical outcomes are increasingly tracked by health care institutions, governments, and payers, and efforts are underway for utilizing outcomes as the basis of payment as part of pay-for-performance [50]. Consistent with the triple aim [51] and health reform [52], as payment hinges increasingly on health outcomes, rather than the volume of service rendered, this technology can be employed with efforts to optimize MA so as to maximize the potential of achieving clinical outcomes, especially for patients exhibiting or at risk for NA.…”
Section: Original Researchmentioning
confidence: 99%
“…[4] Another study examining the impact of P4P programs in acute care hospitals found that P4P hospitals were more likely than control group hospitals to achieve high performance scores during the first 5 years of program implementation. [6] Performance scores reflected whether the hospital met or exceeded specified standards of care in treating a number of disease conditions, including pneumonia, heart failure, myocardial infarction, and hip and knee replacements. In addition, the most dramatic improvements in care quality were found in P4P hospitals that operated in less competitive markets, had strong financial performance, and employed large financial incentives.…”
Section: Introductionmentioning
confidence: 99%